Frontispiece: Organosulfonate Counteranions—A Trapped Coordination Polymer as a High‐Output Triboelectric Nanogenerator Material for Self‐Powered Anticorrosion. Issue 3 (22nd January 2020) - Zhang, Yingying; Wu, Jiarui; Cui, Siwen; Wei, Wutao; Chen, Weihua; Pang, Rui; Wu, Zijie; Mi, Liwei
Abstract : A triboelectric nanogenerator based on a metal‐organic coordination polymer (MOCP) was achieved, exhibiting high‐output performance for practical applications. MOCP powder with electron‐donating ability injected electrons to the organic polymer layer when the two friction layers contacted with each other. For more information, see the Communication by R. Pang and L. Mi et al. on page 584 ff.